Ipsilateral and contralateral torque responses to bilateral and unilateral maximal, fatiguing, isokinetic leg extensions - Neltner, T. J.; Anders, J. P. V.; Keller, J. L.; Smith, R. W.; Housh, T. J.; Schmidt, R. J.; Johnson, G. O. (International Journal of Kinesiology & Sports Science, 2020)
Background: Few studies have compared performance fatigability (PF) for bilateral versus unilateral isokinetic tasks. Objectives: The purpose of this study was to examine: Mode-specific testing responses to isokinetic fatigue, differences in PF between bilateral and unilateral leg extensions, and the effects of fatiguing, unilateral, dynamic leg extensions on contralateral isokinetic peak torque (PT) and maximal voluntary isometric contraction (MVIC). Methods: Eight men (mean ± SD: age= 22.5 ± 2.5 yr.) completed pre- and post-testing for PT and MVIC following 50 bilateral, unilateral right or left leg maximal, isokinetic leg extensions at 180°·s-1, on three separate days. Fatigue-induced decreases in PT and MVIC were used to quantify PF. The data were analyzed with a 4-way repeated measures ANOVA, follow up, and post-hoc analyses. Results: The results indicated that there were no differences (p > 0.05) in PF for the bilateral versus unilateral fatiguing tasks, decreases in PT (p < 0.001 - 0.016; d = 0.54 - 2.58) and MVIC (p < 0.001 - 0.006; Eta 2p = 0.682 - 0.962) for the exercised legs during unilateral fatigue, and a contralateral increase (p = 0.007) in PT following the right leg fatiguing task. Conclusion: The results indicated that PT was more sensitive to fatiguing isokinetic tasks than was MVIC. In addition, there was a facilitation of PT in the contralateral leg following unilateral right leg fatigue. The differences in PT and MVIC testing may be attributable to the timing and/or relative contributions of peripheral and central fatigue.